2001
DOI: 10.1016/s0035-9203(01)90036-7
|View full text |Cite
|
Sign up to set email alerts
|

Complement binding to erythrocytes is associated with macrophage activation and reduced haemoglobin in Plasmodium falciparum malaria

Abstract: We have examined IgG and complement factor C3d deposition on erythrocytes by means of the direct Coombs' test (DAT) and looked for an association with the anaemia seen in falciparum malaria in children living in an area of hyperendemic malaria transmission (in Ghana). In one study (in 1997), 53 out of 199 patients had a positive DAT. Of these, 45 samples reacted with anti-C3d antibodies, 2 with anti-IgG and 6 with both reagents. There were significantly lower haemoglobin (Hb)-levels and higher prevalence of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 30 publications
2
32
2
Order By: Relevance
“…The involvement of complement in Plasmodium infections has been widely reported in malaria literature (10, 112, 113) and extensively reviewed elsewhere (114). Different reports have demonstrated that during ma-laria, complement activation is increased (115,116). Thus, it is necessary that the host complement regulatory proteins, molecules that protect normal cells from autologous complement-mediated lysis, are expressed in sufficient levels to control complement activation on the cell surface and thereby maintain physiological homeostasis (117).…”
Section: The Complement System and Malariamentioning
confidence: 99%
“…The involvement of complement in Plasmodium infections has been widely reported in malaria literature (10, 112, 113) and extensively reviewed elsewhere (114). Different reports have demonstrated that during ma-laria, complement activation is increased (115,116). Thus, it is necessary that the host complement regulatory proteins, molecules that protect normal cells from autologous complement-mediated lysis, are expressed in sufficient levels to control complement activation on the cell surface and thereby maintain physiological homeostasis (117).…”
Section: The Complement System and Malariamentioning
confidence: 99%
“…IgG and complement C3 have been detected on erythrocytes from malaria patients with severe anemia. [30][31][32][33] We demonstrate here that RSP2 has features consistent with a key role in the development of anemia. Tagging RSP2-tagged erythrocytes with a cytophilic anti-RSP2 mAb and sera from immune malaria patients triggered phagocytosis by adherent human monocytes, whereas such phagocytosis was less common in the absence of noncytophilic IgG3 (with mAb D10) or nonimmune human sera.…”
Section: Discussionmentioning
confidence: 94%
“…This possibility has been raised before, when the deposition of surface IgG and changes in the surface expression of complement regulatory protein are correlated with severe malarial anemia. 31,32 However, no specific target antigen was identified that could trigger this reaction. Rigidification of the membrane of RSP2-tagged erythrocytes may lead to cell destruction, even in the absence of antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] In addition, in patients with paroxysmal nocturnal hemoglobinuria (PNH) syndrome, the observed intravascular hemolysis is due to increased sensitivity of RBCs to autologous complement-mediated lysis. 26,27 It is generally believed that the lack of CD59, which inhibits the assembly of the membrane-attack complex C5b-C9 by interacting with C8 and C9, 28,29 is most likely responsible for the increased sensitivity of PNH RBCs and platelets to complement.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…7 Complement-mediated intravascular and extravascular destruction of RBCs has been implicated as a contributing cause of anemia associated with sickle cell disease (SCD) [8][9][10][11][12][13][14][15][16][17][18] and in severe malarial infection. [19][20][21][22][23][24][25] In addition, in patients with paroxysmal nocturnal hemoglobinuria (PNH) syndrome, the observed intravascular hemolysis is due to increased sensitivity of RBCs to autologous complement-mediated lysis. 26,27 It is generally believed that the lack of CD59, which inhibits the assembly of the membrane-attack complex C5b-C9 by interacting with C8 and C9, 28,29 is most likely responsible for the increased sensitivity of PNH RBCs and platelets to complement.…”
Section: The Complement System In Transfusion Medicinementioning
confidence: 99%